The role of nitric oxide in the regulation of the systemic and pulmonary vasculature of the rattlesnake, Crotalus durissus terrificus - Galli, G. L. J.; Skovgaard, N.; Abe, Augusto Shinya [UNESP]; Taylor, E. W.; Wang, T. (Springer, 2005)
The functional role of nitric oxide (NO) was investigated in the systemic and pulmonary circulations of the South American rattlesnake, Crotalus durissus terrificus. Bolus, intra-arterial injections of the NO donor, sodium nitroprusside (SNP) caused a significant systemic vasodilatation resulting in a reduction in systemic resistance (Rsys). This response was accompanied by a significant decrease in systemic pressure and a rise in systemic blood flow. Pulmonary resistance (Rpul) remained constant while pulmonary pressure (Ppul) and pulmonary blood flow (Qpul) decreased. Injection of L-Arginine (L-Arg) produced a similar response to SNP in the systemic circulation, inducing an immediate systemic vasodilatation, while Rpul was unaffected. Blockade of NO synthesis via the nitric oxide synthase inhibitor, L-NAME, did not affect haemodynamic variables in the systemic circulation, indicating a small contribution of NO to the basal regulation of systemic vascular resistance. Similarly, Rpul and Qpul remained unchanged, although there was a significant rise in Ppul. Via injection of SNP, this study clearly demonstrates that NO causes a systemic vasodilatation in the rattlesnake, indicating that NO may contribute in the regulation of systemic vascular resistance. In contrast, the pulmonary vasculature seems far less responsive to NO.